Metal oxide semiconductor fiber gas sensor as well as preparation method and application thereof
By using alloy fibers covering the insulating layer as the substrate, combining the metal oxide semiconductor gas-sensitive layer and the heating electrode, the problems of high power consumption, poor flexibility and low thermal efficiency of the sensor are solved, and a gas sensor with miniaturization, good flexibility and low thermal loss are achieved.
Patent Information
- Application Number
- CN202411734341.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The existing metal oxide semiconductor gas sensors have problems such as high power consumption, poor flexibility, low thermal efficiency and large volume, which limits their application in low-power scenarios and wearable devices.
The alloy fibers covered with an insulating layer are used as the substrate. The surface of the alloy fiber is covered with an insulating layer except for both ends, the surface of the insulating layer is covered with a metal oxide semiconductor gas-sensitive layer, a gas detection electrode is arranged at both ends of the insulating layer, and a heating electrode is arranged at both ends of the alloy fiber.
It realizes the miniaturization of the sensor, good flexibility and low heat loss, reduces power consumption, and is suitable for low-power scenarios and wearable devices.
Smart Images

Figure HDA0005161092930000011 
Figure HDA0005161092930000012 
Figure HDA0005161092930000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas sensors, and in particular to a metal oxide semiconductor fiber gas sensor, a preparation method thereof and a sensor system. Background Art
[0002] A gas sensor is a converter that can convert the concentration of a gas into a corresponding electrical signal. Gas sensors can be divided into semiconductor gas sensors, solid electrolyte gas sensors, contact combustion gas sensors, electrochemical gas sensors, and optical gas sensors according to their working principles.
[0003] Metal oxide semiconductor gas sensors are a type of semiconductor gas sensors. They have been widely used in many fields due to their advantages such as fast response, high sensitivity, simple process, low energy consumption and low cost. For example, ZnO, SnO2, WO3, Fe2O3, NiO, etc. have been developed as gas-sensitive materials. At present, common metal oxide semiconductor gas sensors are gas-sensitive materials dispersed in deionized water or ethanol, made into slurry and directly coated on a ceramic tube substrate or directly grown on a hard substrate such as a micro-electromechanical system (MEMS).
[0004] For gas sensors with ceramic tube structures, nickel-chromium heating wires are generally placed inside the ceramic tube, and the gas-sensitive material is dispersed and coated on the surface of the ceramic tube with ethanol or deionized water. The gas sensor made in this way consumes a lot of electrical energy during heating, resulting in a high overall power consumption of the sensor. High power consumption not only increases the cost of use, but also limits its application in low-power scenarios; at the same time, during the heating process, part of the heat energy will be dissipated in the form of thermal radiation, heat conduction, etc., resulting in reduced thermal efficiency. The ceramic tube structure itself has a certain rigidity and brittleness, and is difficult to bend or fold, which limits the application of sensors in flexible or wearable devices. Therefore, in application scenarios that require high integration and portability, this rigid structure may become a restrictive factor. On the other hand, sensors with ceramic tube structures are usually large in size and heavy in weight, which is not conducive to achieving lightweight and portability of the device. Due to the limitations of the ceramic tube structure, gas sensors may have certain difficulties in integrating with other electronic components or systems, which may increase the complexity and cost of the entire system, and may also limit the application of sensors in a wider range of fields.
[0005] For MEMS gas sensors, in order to reduce power consumption and achieve structural insulation, insulation grooves are generally used. At present, the structure commonly used in silicon-based gas sensors made based on MEMS technology is as follows: a silicon nitride film layer is deposited on the upper surface of a single-crystal silicon substrate as a lower insulating layer, and an insulation groove is prepared on the lower surface of the single-crystal silicon substrate; when preparing the insulation groove, a backside wet etching process can be used, or a cantilever beam can be first etched out of the lower insulation layer, and then an inverted pyramid insulation groove is wet-etched downward. The two insulation grooves can better prevent heat loss to reduce power consumption; a platinum heating wire layer is processed above the lower insulation layer by a lift-off process, and heat can be generated by energizing the heating wire to form the temperature required for the gas sensor to work; a silicon nitride layer is deposited on the surface of the platinum heating wire as an upper insulating layer, and finally a temperature sensitive layer and a gas sensitive layer are deposited. However, after etching the insulation groove in this method, the heating layer and the gas sensitive layer are supported by only a thin film structure of silicon nitride layer, and the thin film is only supported by the supporting substrate of the cantilever structure at both ends, and the mechanical properties are poor. When the device is vibrated or collided, it is easy to break and cause the device to fail. In addition, due to the difference in thermal expansion coefficients between the insulation layer and the heating wire, the insulation layer is prone to warping at high temperatures, making it easy for the heating wire to fall off the insulation layer, which also leads to device failure. Secondly, the insulation groove of the cantilever structure uses the air between the cantilevers for thermal insulation. Due to the large space and fast air flow, heat will also be lost quickly, affecting the insulation effect. Thirdly, the preparation process of this type of insulation groove is complicated and requires high control conditions, which increases the difficulty of processing.
[0006] In order to solve the above problems, providing a metal oxide gas sensor with small size, good flexibility and low heat loss is of great significance for realizing its wide application. Summary of the invention
[0007] The technical problem solved by the present invention is to provide a metal oxide semiconductor fiber gas sensor. The sensor provided by the present application has the advantages of miniaturization, good flexibility and low heat loss.
[0008] In view of this, the present application provides a metal oxide semiconductor fiber gas sensor, comprising: an alloy fiber, an insulating layer, a gas detection electrode, a metal oxide semiconductor gas sensitive layer and a heating electrode;
[0009] The surface of the alloy fiber, except for the two ends, is covered with the insulating layer;
[0010] The surface of the insulating layer is coated with a metal oxide semiconductor gas-sensitive layer;
[0011] The gas detection electrodes are arranged at both ends of the insulating layer;
[0012] The heating electrodes are arranged at both ends of the alloy fiber.
[0013] Preferably, the alloy fiber is selected from nickel-chromium alloy wire, copper wire, silver wire or iron-carbon alloy wire, and the diameter of the alloy fiber is ≥5 μm.
[0014] Preferably, the insulating layer is a silica microsphere coating layer, an alumina microsphere coating layer or a polymer coating layer, and the thickness of the insulating layer is ≥1 μm.
[0015] Preferably, the gas detection electrode comprises a silver wire, a platinum wire or a gold wire, and the heating electrode comprises a silver wire, a platinum wire or a gold wire.
[0016] Preferably, the metal oxide of the metal oxide semiconductor gas-sensitive layer includes zinc oxide, tin dioxide, tungsten trioxide, titanium dioxide, iron oxide or the above oxides doped with metals.
[0017] The present application also provides a method for preparing a metal oxide semiconductor fiber gas sensor, comprising the following steps:
[0018] S1) forming an insulating layer on the surface of the alloy fiber, and leaving both ends of the alloy fiber bare, to obtain an alloy fiber with the outer surface of both ends covered with the insulating layer;
[0019] S2) forming gas detection electrodes at both ends of the insulating layer;
[0020] forming a metal oxide semiconductor gas-sensitive layer on the surface of the insulating layer;
[0021] S3) Connecting heating electrodes at both ends of the alloy fiber to obtain a metal oxide semiconductor fiber gas sensor.
[0022] Preferably, the method for preparing the alloy fiber having an insulating layer coated on the outer surfaces except the two ends is specifically as follows:
[0023] The insulating microsphere dispersion is prepared by a sol-gel method; the insulating microsphere dispersion is a silicon dioxide microsphere dispersion or an aluminum oxide microsphere dispersion;
[0024] The alloy fiber is immersed in the insulating microsphere dispersion liquid by the immersion and pulling method, and then pulled, and the alloy fiber with the microsphere insulating layer coated on the surface is obtained after heating;
[0025] The insulating microspheres at both ends of the alloy fiber whose surface is coated with the microsphere insulating layer are removed to obtain the alloy fiber whose outer surface except the two ends is coated with the microsphere insulating layer.
[0026] Preferably, the alloy fiber is prepared by sequentially performing metal raw material smelting, homogenization annealing, forging and cold drawing.
[0027] Preferably, the metal oxide semiconductor gas-sensitive layer is prepared by atomic layer deposition, hydrothermal method, sol-gel method, electrospinning method, vapor deposition method or magnetron sputtering method.
[0028] The present application also provides a sensor system, comprising the metal oxide semiconductor fiber gas sensor or the metal oxide semiconductor fiber gas sensor prepared by the preparation method.
[0029] The present application provides a metal oxide semiconductor fiber gas sensor, which includes an alloy fiber, an insulating layer, a gas detection electrode, a metal oxide semiconductor gas sensitive layer and a heating electrode; wherein, the surface of the alloy fiber is coated with an insulating layer except for the two ends, the surface of the insulating layer is coated with the metal oxide semiconductor gas sensitive layer, the gas detection electrodes are arranged at the two ends of the insulating layer, and the heating electrodes are arranged at the two ends of the alloy fiber; in the metal oxide semiconductor fiber gas sensor provided by the present application, the alloy fiber coated with the insulating layer realizes the miniaturization of the sensor, and the introduction of the alloy fiber makes the gas sensor have better flexibility, the surface of the alloy fiber is coated with the insulating layer so that after the external current is applied, the Joule heat generated by the alloy fiber realizes the direct heating of the metal oxide semiconductor gas sensitive layer, so that the metal oxide semiconductor gas sensitive layer can work at the optimal sensing temperature, thereby reducing the heat loss of the metal oxide semiconductor fiber gas sensor. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a flow chart of the preparation of the alloy fiber of the present invention;
[0031] Figure 2 is a flow chart for preparing the insulating layer of the present invention;
[0032] Figure 3 The figure is a flow chart of the preparation of the metal oxide semiconductor fiber gas sensor of the present invention;
[0033] Figure 4 This is a SEM photograph of Co-doped ZnO nanorods in the metal oxide semiconductor gas sensing layer prepared in Example 1 of the present invention;
[0034] Figure 5 This is a curve diagram of the resistance change in response to methane of the metal oxide semiconductor fiber gas sensor prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0036] In view of the performance requirements of metal oxide semiconductor gas sensors in the prior art for small size, good flexibility and low heat loss, the present application provides a metal oxide semiconductor fiber gas sensor, which achieves the advantages of sensor miniaturization, flexibility and low power consumption by introducing alloy fibers coated with an insulating layer. The key point of the present application is that the substrate is different from the traditional ceramic tube and MEMS substrate. The substrate adopts homemade microspheres coated with alloy fibers, and metal oxide gas-sensitive materials are grown in situ, so that the sensor has good flexibility, small size, low heat loss, low cost, and easy integration, which can be well applied in the field of wearable gas sensors. Specifically, an embodiment of the present invention discloses a metal oxide semiconductor fiber gas sensor, including: alloy fibers, an insulating layer, a gas detection electrode, a metal oxide semiconductor gas-sensitive layer and a heating electrode;
[0037] The surface of the alloy fiber, except for the two ends, is covered with the insulating layer;
[0038] The surface of the insulating layer is coated with a metal oxide semiconductor gas-sensitive layer;
[0039] The gas detection electrodes are arranged at both ends of the insulating layer;
[0040] The heating electrodes are arranged at both ends of the alloy fiber.
[0041] In the metal oxide semiconductor fiber gas sensor provided in the present application, the surface of the alloy fiber is coated with an insulating layer except for the two ends, that is, the two ends of the alloy fiber are exposed, and the other surfaces are coated with an insulating layer; the alloy fiber generates Joule heat after an external current is provided, which can heat the metal oxide semiconductor gas-sensitive layer, so that the metal oxide semiconductor gas-sensitive layer works at the optimal sensing temperature. The alloy fiber can be selected from conductive and thermal conductive alloy fibers. Specifically, the alloy fiber is selected from nickel-chromium alloy wire, copper wire, silver wire or iron-carbon alloy wire; the specific material ratio of the above alloy fiber is well known to those skilled in the art, and this application does not impose any special restrictions on this; the diameter of the alloy fiber is ≥5μm, specifically, the diameter of the alloy fiber is 30-80μm, and more specifically, the diameter of the alloy fiber is 45-70μm; the preparation method of the alloy fiber is not particularly limited in this application, and it can be prepared by cold drawing. The insulating layer provides a substrate for the growth of the metal oxide semiconductor gas-sensitive layer, isolates the metal oxide semiconductor gas-sensitive layer and the alloy fiber, and achieves the role of an insulating thermally conductive substrate; as mentioned above, the insulating layer can achieve the role of insulating the metal oxide semiconductor gas-sensitive layer and the alloy fiber. For example, the insulating layer is a silica microsphere insulating layer, an alumina microsphere insulating layer or a polymer insulating layer, wherein the polymer insulating layer is a PDMS insulating layer, a Teflon insulating layer, etc., and the thickness of the insulating layer is ≥1μm, specifically, the thickness of the insulating layer is 30 to 80μm, and more specifically, the thickness of the insulating layer is 50 to 70μm. The insulating layer can be coated on the surface of the alloy fiber by an immersion pulling method.
[0042] In the present application, the surface of the insulating layer is coated with a metal oxide semiconductor gas-sensitive layer; the metal oxide in the metal oxide semiconductor gas-sensitive layer serves as a gas-sensitive material, providing a site for the adsorption of the target gas to achieve the purpose of detecting the target gas. The metal oxide of the metal oxide semiconductor gas-sensitive layer includes zinc oxide, tin dioxide, tungsten trioxide, titanium dioxide, iron oxide, or the above oxides doped with metals, for example, cobalt-doped zinc oxide.
[0043] The gas detection electrodes are arranged at both ends of the insulating layer to detect the resistance of the metal oxide semiconductor gas-sensitive layer, convert the interaction between the target gas and the metal oxide in the gas-sensitive layer into a change in resistance, and realize gas detection. The gas detection electrodes include silver wires, platinum wires or gold wires.
[0044] The heating electrodes are arranged at both ends of the alloy fiber to apply current to the alloy fiber so that the alloy fiber generates Joule heat. The heating electrodes include silver wire, platinum wire or gold wire; the materials of the gas detection electrode and the heating electrode can be the same or different, and this application does not impose any special restrictions on this.
[0045] In the metal oxide semiconductor fiber gas sensor provided in the present application, the above-mentioned two ends are relative to the middle part, and there is no special restriction on the specific positions of the two ends.
[0046] Furthermore, the present application also provides a method for preparing a metal oxide semiconductor fiber gas sensor, comprising the following steps:
[0047] S1) forming an insulating layer on the surface of the alloy fiber, and leaving both ends of the alloy fiber bare, to obtain an alloy fiber with the outer surface of both ends covered with the insulating layer;
[0048] S2) forming gas detection electrodes at both ends of the insulating layer;
[0049] forming a metal oxide semiconductor gas-sensitive layer on the surface of the insulating layer;
[0050] S3) Connecting heating electrodes at both ends of the alloy fiber to obtain a metal oxide semiconductor fiber gas sensor.
[0051] In the preparation process of the metal oxide semiconductor fiber gas sensor, the present application first forms an insulating layer on the surface of the alloy fiber, and exposes both ends of the alloy fiber to obtain an alloy fiber with an insulating layer on the outer surface except for the two ends; in the above process, the alloy fiber can be prepared first, and the schematic diagram of the preparation process of the alloy fiber is as follows Figure 1 As shown, Figure 1 In the figure, 1 is an induction furnace, 2 is a forging process, 3 is a cold rolling process, 4 is a preformed rod after cold rolling, 5 is a wire feeding device, 6 is lubricating oil, 7 is a cold drawing die, 8 is an alloy fiber, and 9 is a capstan; that is, the present application preferably prepares the alloy fiber by cold drawing. Specifically, the alloy fiber is prepared by sequentially carrying out metal raw material smelting, homogenizing annealing, forging and cold drawing.
[0052] According to the present invention, an insulating layer is formed on the surface of the alloy fiber; the method for preparing the microsphere insulating layer in the insulating layer is specifically as follows: preferably, a sol-gel method is used to prepare an insulating microsphere dispersion liquid, and then an immersion and pulling method is used to prepare an insulating microsphere-coated alloy fiber; the flow diagram is shown in FIG. Figure 2 As shown, Figure 2 10 is a microsphere precursor sol, 11 is a microsphere precursor gel, 12 is a dried microsphere, 13 is a microsphere dispersion, 14 is an alloy fiber, and 15 is an alloy fiber coated with microspheres; on this basis, the preparation method of the alloy fiber coated with an insulating layer on both ends of the outer surface of the present application is specifically as follows:
[0053] The insulating microsphere dispersion is prepared by a sol-gel method; the insulating microsphere dispersion is a silicon dioxide microsphere dispersion or an aluminum oxide microsphere dispersion;
[0054] The alloy fiber is immersed in the insulating microsphere dispersion liquid and then pulled by the immersion pulling method to obtain the insulating microsphere-coated alloy fiber;
[0055] The insulating microspheres at both ends of the insulating microsphere-coated alloy fiber are removed to obtain an alloy fiber with the outer surfaces except the two ends coated with the microsphere insulating layer.
[0056] In the above preparation process, the pulling speed is 1-10 cm / min, specifically, the pulling speed is 2-7 cm / min; the heating temperature is 200-250°C, the time is 1-5 hours, specifically, the heating temperature is 220-240°C, and the time is 2-4 hours. The method for removing the insulating microspheres at both ends of the alloy fiber is a method well known to those skilled in the art, for example, an organic solvent can be used to remove the microspheres at both ends of the alloy fiber, and further, acetone can be used to remove the microspheres at both ends of the alloy fiber.
[0057] The present application then forms gas detection electrodes at both ends of the insulating layer, specifically, the gas detection electrodes are respectively wound around the two ends of the insulating layer, and then the conductive metal paste is coated on the connection between the gas detection electrode and the insulating layer, and then annealed to sinter it together with the gas detection electrode; in the above process, the material selection of the gas detection electrode and the conductive metal paste can be the same. In some specific embodiments, the gas detection electrode is a silver wire, and the conductive metal paste is a silver paste.
[0058] According to the present invention, a metal oxide semiconductor gas-sensitive layer is then formed on the surface of the insulating layer, and the metal oxide semiconductor gas-sensitive layer is prepared by atomic layer deposition, hydrothermal method, sol-gel method, electrospinning method, vapor deposition method or magnetron sputtering method; in a specific embodiment, Co-doped ZnO nanorods can be in-situ grown on the surface of the insulating layer by a hydrothermal method, firstly, ZnO nanoparticles are coated on the insulating layer by a sol-gel method to form a seed layer, and then Co-doped ZnO nanorods are grown by a hydrothermal method.
[0059] Finally, the present application connects heating electrodes at both ends of the alloy fiber, and applies a thermal conductive slurry to the connection between the heating electrode and the alloy fiber. After annealing, the alloy fiber and the heating electrode are sintered together to finally obtain a metal oxide semiconductor fiber gas sensor; the annealing temperature is 100-200°C, and the time is 10-30 minutes; specifically, the annealing temperature is 120-180°C, and the time is 15-25 minutes.
[0060] The schematic diagram of the preparation process of the metal oxide semiconductor fiber gas sensor of this application is as follows Figure 3 As shown in the figure, 16 is an alloy fiber covered with an insulating layer with both ends exposed, 17 is a gas detection electrode, 18 is a metal oxide semiconductor gas sensitive layer, and 19 is a heating electrode. Figure 3As shown, in the preparation process of the metal oxide semiconductor fiber gas sensor, an alloy fiber coated with an insulating layer is first prepared, then a gas detection electrode is prepared at both ends of the insulating layer, and then a metal oxide semiconductor gas sensitive layer is prepared on the surface of the insulating layer, and finally a heating electrode is prepared at both ends of the alloy fiber.
[0061] The present application also provides a sensor system, which includes the metal oxide semiconductor fiber gas sensor described in the above solution.
[0062] The metal oxide gas sensor provided in the present application can be used alone to detect the concentration of the gas, and can also be integrated with other components to still play its own role, while other components can play their respective roles to form a sensor system with multiple functions.
[0063] The substrate of the metal oxide semiconductor fiber gas sensor provided by the present invention is different from traditional ceramic tubes and MEMS gas sensors. Among them, traditional ceramic tube gas sensors are large in size, poor in flexibility, and high in heat loss, and cannot be well applied in the wearable field. The present application uses microsphere-coated alloy fibers as the substrate, and directly grows gas-sensitive materials in situ on the microsphere-coated alloy fibers, so that the obtained gas sensor is small in size, good in flexibility, low in heat loss, and simple in process, so that it can be well applied in the field of wearable gas sensors.
[0064] In order to further understand the present invention, the metal oxide semiconductor fiber gas sensor and its preparation method provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0065] Example 1
[0066] This embodiment provides a fiber-based metal oxide semiconductor fiber gas sensor, and the preparation process is as follows:
[0067] (1) Preparation of nickel-chromium alloy fibers
[0068] Prepare raw materials according to the composition ratio of C≤0.08%, Mn≤0.6%, P≤0.02%, S≤0.015%, Si: 0.75~1.60%, Cr: 20.0~23.0%, Ni: balance, Fe≤1.0%, Al≤0.5%, smelt nickel and chromium, and homogenize anneal in inert gas at a temperature of 600~750℃. The annealing process is divided into three stages. The first stage is 750℃, and the temperature is controlled to decrease at a rate of 15℃ / min. The second stage is continuously reduced from 700℃ and The temperature is maintained for 10 minutes, and then the temperature is continuously reduced. The third step starts from 650°C and continues to decrease until it reaches 600°C. The annealed ingot is placed in a forging machine and repeatedly forged to obtain an alloy rod with a diameter of 2 mm. Finally, the alloy rod is cold-drawn to a smaller size at a drawing speed of 4 m / min. After ten cold-drawing passes, the cold-drawn wire is annealed at 900°C for about 15 minutes after every two passes. Several wire drawing processes are performed during the drawing process. After each drawing, the elongation of the alloy wire is about 30%, and a nickel-chromium alloy fiber with a diameter of 45 μm is obtained.
[0069] (2) Preparation of microsphere-coated nickel-chromium alloy fibers
[0070] Using TEOS and MTMS as co-precursors as raw materials, under dry conditions at room temperature and pressure, using TEOS and MTMS as co-precursors as raw materials, a base-catalyzed sol-gel method was used to prepare a silica aerogel adsorbent, and the mixture was dried in an environment; MTMS-TEOS:CH3OH:H2O was added to a beaker at a molar ratio of 1:19.1:4.31, and 0.5mL of 0.1mol / L hydrochloric acid solution was added, and the mixture was stirred at room temperature for 1h to promote the hydrolysis reaction; then 0.5mol / L of ammonia water and DMF were added and continued to stir, and the condensation reaction was carried out for a period of time, and the sol was waited to complete the gelation and transform into a wet gel; the wet gel was aged at room temperature for 24h, and then dried at 50°C in a vacuum drying oven for 24h to obtain a silica aerogel; 0.05g of the silica aerogel was dispersed in 2mL of THF containing 10% PS, and stirred for 30min to form a silica microsphere dispersion;
[0071] The alloy wire was cut into small segments of 3 cm, and the nickel-chromium alloy fiber was fixed on an impregnation and pulling machine using a customized clamp. The silica microsphere dispersion in the beaker was placed under the alloy fiber, and the pulling height was controlled so that the alloy fiber was immersed in the silica slurry for 1 minute. The nickel-chromium alloy fiber was pulled at a pulling speed of 1 cm / min, at which time a white coating appeared on the surface of the nickel-chromium alloy fiber, and then heated at 220°C for 1 hour to obtain a nickel-chromium alloy fiber coated with silica microspheres. The diameter of the nickel-chromium alloy fiber was 45 μm, and the thickness of the microsphere insulating layer was 50 μm.
[0072] (3) Preparation of metal oxide semiconductor fiber gas sensors
[0073] The two ends of the nickel-chromium alloy fiber coated with silica microspheres were immersed in acetone for 5 mm, and the excess silica microspheres at both ends were removed to form microsphere-coated alloy fibers with both ends exposed; silver wires with a diameter of 100 μm were respectively wrapped around the two ends of the microsphere insulation layer as gas detection electrodes, and then conductive silver paste was coated on the connection between the silver wire and the microsphere insulation layer, annealed at 450°C for 15 minutes, and sintered together with the silver wire;
[0074] Co-doped ZnO nanorods were grown using a hydrothermal method: first, ZnO nanoparticles were coated on the fiber using a sol-gel method to form a seed layer. The process of producing the ZnO seed layer was as follows:
[0075] 0.16 g (30 mM) zinc acetate (Zn(CH3COO)2·2H2O) was weighed on a balance and dissolved in 25 mL of anhydrous ethanol solution, stirred for 1 h to form a sol-gel system; the nickel-chromium alloy fiber with electrodes obtained above was treated in a vacuum plasma instrument for 90 s to activate the surface and increase hydrophilicity, so that the ZnO seed solution can be more easily attached to the fiber surface. Since the fiber is a one-dimensional shape, the ZnO nanoparticles with dense crystallization and uniform thickness are formed on the fiber surface by the pulling method. The fiber is fixed on the impregnation pulling machine by a clamp, the seed solution in the beaker is placed under the fiber, and the heating coil is fixed between the clamp and the seed solution. The temperature of the heating coil can be accurately controlled by the temperature controller, and the cylindrical heating area inside the heating coil can make the fiber surface heated evenly, and the pulling height is controlled to make the fiber in the seed The fiber was immersed in the seed solution for 2 minutes, at which time the atomic groups on the fiber surface and in the seed solution reached adsorption equilibrium; then the pulling machine was controlled to pull the fiber into the heating circle at a speed of 1 cm / min. During the slow pulling process, the atomic groups formed a uniform and dense film on the fiber surface under the action of surface tension. The temperature of the heating circle was set to 180°C, and the fiber was dried inside the heating circle for 5 minutes to evaporate the organic solvent on the fiber surface and crystallize into ZnO nanoparticles. In order to obtain a uniform and dense ZnO seed layer, the above pulling process was repeated 5 times; finally, the fiber was annealed at 35°C in a muffle furnace for 20 minutes, with a heating rate of 5°C / min. After a dense seed layer grew on the fiber surface, the fiber was placed in a reactor to hydrothermally grow Co-doped ZnO nanorods; the experimental process of growing Co-doped ZnO nanorods is as follows:
[0076] 0.15 g (25 mM) zinc nitrate (Zn(NO3)2·6H2O), 0.07 g (25 mM) hexamethylenetetramine (HMTA) and 0.06 g (10 mM) cobalt nitrate (Co(NO3)2·6H2O) were weighed on a balance and dissolved in 20 mL of deionized water solution. The prepared solution was placed on a constant temperature magnetic stirrer and stirred for 1 hour. The growth solution was poured into the reactor. At the same time, the fiber prepared above was tilted and placed in the reactor to ensure that the fiber and the solution were fully in contact. The reactor was sealed and placed in a muffle furnace and heated at 90°C for 8 hours. After the reaction was completed, the fiber was taken out and the nanorods deposited on the fiber surface clusters were rinsed with deionized water. The fiber was placed in an oven at 60°C for 6 hours to evaporate excess water, and then annealed at 400°C for 2 hours. The two ends of the prepared fiber with uniformly grown metal oxide semiconductors were immersed in a hydrochloric acid solution to remove excess zinc oxide at both ends of the fiber to prevent the heating electrode and zinc oxide from being connected in series. The SEM photo of Co-doped ZnO in the metal oxide semiconductor gas-sensitive layer prepared above is shown in FIG. Figure 4 It can be seen that the metal oxide Co-doped ZnO has a nanorod structure;
[0077] Then, silver wires with a diameter of 100 μm were connected to the cross sections at both ends of the nickel-chromium alloy fiber, and silver paste was applied to the connection between the silver wire and the nickel-chromium alloy fiber. The fiber and the silver wire were annealed at 150°C for 15 minutes in a tube furnace to sinter the fiber and the silver wire together. Through high-temperature sintering of the silver paste, the solid particles are bonded to each other, the grains grow, the gaps and grain boundaries gradually decrease, and through the transfer of substances, the total volume shrinks, the density increases, the silver element crystallizes, the contact resistance is reduced, and an ideal ohmic contact is formed. The microscopic morphology of the metal oxide layer is observed, and the response of the metal oxide semiconductor fiber gas sensor to methane gas is tested, such as Figure 5 As shown, Figure 5 This is the resistance change curve of detecting 500ppm methane at 50℃. Figure 5 It can be seen that the metal oxide semiconductor fiber gas sensor prepared in this embodiment has good responsiveness to methane.
[0078] Example 2
[0079] (1) Preparation of Fe-Cr-Al alloy fibers
[0080] Prepare raw materials according to 23-26wt% of Cr, 4-6wt% of Al, 3-5wt% of V, Fe (carbon content ≤ 0.02wt%), 0.3-0.5wt% of Y and 0.1-0.5wt% of Nb; melt Fe, Cr, Al, V, Y and Nb in order under vacuum conditions, cast the solution into alloy ingots, forge the alloy ingots for multiple times, and then roll them into alloy rods, and anneal them in an argon atmosphere at a temperature of 900°C; draw the alloy rods in multiple passes, the diameter of the alloy wire can be determined according to the number of drawing processes and the size of the die, the diameter of the prepared alloy rods is 1mm, the drawing speed is 4m / min, and after each cold drawing, the cold drawn wire is annealed at 700°C for about 30min; perform several wire drawing processes during the drawing process, and finally obtain 45μm iron-chromium-aluminum alloy fibers;
[0081] (2) Preparation of microsphere-coated Fe-Cr-Al fibers
[0082] Aluminum isopropoxide was used as a raw material to prepare alumina microspheres: the molar ratio of aluminum isopropoxide: H2O: HNO3 was 1:100:0.3, 8.17 g of isopropanol was weighed and dissolved in 72 mL of deionized water, and stirred and hydrolyzed for 2 h in a water bath at a temperature of 85 ° C, and then a certain amount of dilute nitric acid with a concentration of 2 mol / L was added and stirred for 1 h to obtain alumina wet gel, which was aged at room temperature for 24 h, and then dried in an oven at 60 ° C for 24 h, and the obtained alumina microspheres were dispersed in a specific dispersion to prepare an alumina microsphere dispersion for immersion pulling;
[0083] The alloy fiber was cut into small segments of 3 cm, and the iron-chromium-aluminum alloy fiber was fixed on an impregnation and pulling machine using a customized clamp. The alumina microsphere dispersion in the beaker was placed under the alloy fiber, and the pulling height was controlled so that the alloy fiber was immersed in the silica slurry for 1 minute. The iron-chromium-aluminum alloy fiber was pulled at a pulling speed of 1 cm / min, at which time a white coating appeared on the surface of the iron-chromium-aluminum alloy fiber, and then heated at 220°C for 1 hour to obtain the iron-chromium-aluminum alloy fiber coated with alumina microspheres. The diameter of the iron-chromium-aluminum alloy fiber was 45 μm, and the thickness of the microsphere insulating layer was 50 μm.
[0084] The flexibility of the prepared fiber was tested. A 3cm long fiber segment was selected. The bending angle of the fiber could reach 60°, which showed good flexibility. The surface temperature of the iron-chromium-aluminum alloy fiber under different currents was tested. The surface temperature could reach up to 1000°C, which was much higher than the working temperature of the sensor. The heat generated by the iron-chromium-aluminum alloy wire was all transferred to the fiber surface through heat conduction. There was no heat convection loss between the alloy wire and the air. Only a small amount of heat conduction existed in the alumina microsphere cladding.
[0085] (3) Preparation of metal oxide semiconductor fiber gas sensors
[0086] The two ends of the iron-chromium-aluminum alloy fiber coated with alumina microspheres were immersed in acetone for 5 mm, and the excess alumina microspheres at both ends were removed to form microsphere-coated alloy fibers with both ends exposed; silver wires with a diameter of 100 μm were respectively wound around the two ends of the microsphere insulation layer as gas detection electrodes, and then conductive silver paste was coated on the connection between the silver wire and the microsphere insulation layer, annealed at 450°C for 15 minutes, and sintered together with the silver wire;
[0087] Co-doped ZnO nanorods were grown using a hydrothermal method: first, ZnO nanoparticles were coated on the fiber using a sol-gel method to form a seed layer. The process of producing the ZnO seed layer was as follows:
[0088] 0.16 g (30 mM) zinc acetate (Zn(CH3COO)2·2H2O) was weighed on a balance and dissolved in 25 mL of anhydrous ethanol solution, stirred for 1 h to form a sol-gel system; the iron-chromium-aluminum alloy fiber with electrodes obtained above was treated in a vacuum plasma instrument for 90 s to activate the surface and increase hydrophilicity, so that the ZnO seed solution can be more easily attached to the fiber surface. Since the fiber is a one-dimensional shape, the ZnO nanoparticles with dense crystallization and uniform thickness are formed on the fiber surface by the pulling method. The fiber is fixed on the impregnation pulling machine by a clamp, the seed solution in the beaker is placed under the fiber, and the heating coil is fixed between the clamp and the seed solution. The temperature of the heating coil can be accurately controlled by a thermostat and the heating coil is The cylindrical heating area at the bottom can make the fiber surface heated evenly. The pulling height is controlled to make the fiber soak in the seed solution for 2 minutes. At this time, the atomic groups on the fiber surface and in the seed solution reach adsorption equilibrium. Then the pulling machine is controlled to pull the fiber into the heating circle at a speed of 1 cm / min. In the process of slow pulling, the atomic groups form a uniform and dense film on the fiber surface under the action of surface tension. The temperature of the heating circle is set to 180°C. Drying inside the heating circle for 5 minutes makes the organic solvent on the fiber surface evaporate and crystallize into ZnO nanoparticles. In order to obtain a uniform and dense ZnO seed layer, the above pulling process is repeated 5 times. Finally, the fiber is annealed at 35°C in a muffle furnace for 20 minutes, and the heating rate is 5°C / min.
[0089] After a dense seed layer is grown on the fiber surface, the fiber is placed in a reactor to hydrothermally grow Co-doped ZnO nanorods. The experimental process of growing Co-doped ZnO nanorods is as follows:
[0090] Use a balance to weigh 0.15g (25mM) zinc nitrate (Zn(NO3)2·6H2O), 0.07g (25mM) hexamethylenetetramine (HMTA) and 0.06g (10mM) cobalt nitrate (Co(NO3)2·6H2O) and dissolve them in 20mL deionized water solution. Place the prepared solution on a constant temperature magnetic stirrer and stir for 1h. Pour the growth solution into the reactor. At the same time, the prepared fiber is tilted in the reactor to ensure full contact between the fiber and the solution. The reactor is sealed and placed in a muffle furnace and heated at 90℃ for 8h. After the reaction is completed, take out the fiber and rinse with deionized water to remove the nanorods deposited on the fiber surface clusters. Place it in an oven at 60℃ for 6h to evaporate excess water, and then anneal it at 400℃ for 2h.
[0091] The two ends of the prepared fiber with uniformly grown metal oxide semiconductors were immersed in a hydrochloric acid solution to remove excess zinc oxide at both ends of the fiber to prevent the heating electrode and zinc oxide from being connected in series; then silver wires with a diameter of 100 μm were connected to the cross-sections at both ends of the iron-chromium-aluminum alloy fiber, and silver paste was coated on the connection between the silver wire and the iron-chromium-aluminum alloy fiber, and annealed at 150°C for 15 minutes in a tube furnace to sinter the fiber and the silver wire together; through high-temperature sintering of the silver paste, the solid particles are bonded to each other, the grains grow, the gaps and grain boundaries gradually decrease, and through the transfer of matter, the total volume shrinks, the density increases, the silver element crystallizes, the contact resistance is reduced, and an ideal ohmic contact is formed. The microscopic morphology of the metal oxide layer is observed to test the response of the metal oxide semiconductor fiber gas sensor to methane gas.
[0092] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0093] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A metal oxide semiconductor fiber gas sensor, comprising: Alloy fiber, insulating layer, gas detection electrode, metal oxide semiconductor gas sensitive layer and heating electrode; The surface of the alloy fiber, except for the two ends, is covered with the insulating layer; The surface of the insulating layer is coated with a metal oxide semiconductor gas-sensitive layer; The gas detection electrodes are arranged at both ends of the insulating layer; The heating electrodes are arranged at both ends of the alloy fiber.
2. The gas sensor according to claim 1, characterized in that The alloy fiber is selected from nickel-chromium alloy wire, copper wire, silver wire or iron-carbon alloy wire, and the diameter of the alloy fiber is ≥5 μm.
3. The gas sensor according to claim 1, characterized in that: The insulating layer is a silicon dioxide microsphere coating layer, an aluminum oxide microsphere coating layer or a polymer coating layer, and the thickness of the insulating layer is ≥1 μm.
4. The gas sensor according to claim 1, characterized in that: The gas detection electrode includes a silver wire, a platinum wire or a gold wire, and the heating electrode includes a silver wire, a platinum wire or a gold wire.
5. The gas sensor according to claim 1, characterized in that: The metal oxide of the metal oxide semiconductor gas-sensitive layer includes zinc oxide, tin dioxide, tungsten trioxide, titanium dioxide, iron oxide or the above oxides doped with metals.
6. A method for preparing a metal oxide semiconductor fiber gas sensor, comprising the following steps: S1) forming an insulating layer on the surface of the alloy fiber, and leaving both ends of the alloy fiber bare, to obtain an alloy fiber with the outer surface of both ends covered with the insulating layer; S2) forming gas detection electrodes at both ends of the insulating layer; forming a metal oxide semiconductor gas-sensitive layer on the surface of the insulating layer; S3) Connecting heating electrodes at both ends of the alloy fiber to obtain a metal oxide semiconductor fiber gas sensor.
7. The preparation method according to claim 6, characterized in that: The method for preparing the alloy fiber having an insulating layer coated on the outer surfaces of both ends is specifically as follows: The insulating microsphere dispersion is prepared by a sol-gel method; the insulating microsphere dispersion is a silicon dioxide microsphere dispersion or an aluminum oxide microsphere dispersion; The alloy fiber is immersed in the insulating microsphere dispersion liquid by the immersion and pulling method, and then pulled, and the alloy fiber with the microsphere insulating layer coated on the surface is obtained after heating; The insulating microspheres at both ends of the alloy fiber whose surface is coated with the microsphere insulating layer are removed to obtain the alloy fiber whose outer surfaces except the two ends are coated with the microsphere insulating layer.
8. The preparation method according to claim 6 or 7, characterized in that: The alloy fiber is prepared by sequentially performing metal raw material smelting, homogenization annealing, forging and cold drawing.
9. The preparation method according to claim 6 or 7, characterized in that: The metal oxide semiconductor gas-sensitive layer is prepared by atomic layer deposition, hydrothermal method, sol-gel method, electrostatic spinning method, vapor deposition method or magnetron sputtering method.
10. A sensor system, comprising the metal oxide semiconductor fiber gas sensor according to any one of claims 1 to 5 or the metal oxide semiconductor fiber gas sensor prepared by the preparation method according to any one of claims 6 to 9.